Growth Pattern In ′Pure′ Atopic Dermatitis - Saraswat Abir; Handa Sanjeev; Bhalla Anil Kumar; Kumar Bhusan (Wolters Kluwer Medknow Publications, 2002)
A topic dermatitis (AD) in children has been shown to be associated with growth impairment in a few recent studies. There however, has been no report published on the growth pattern of children who have â€˜pureâ€ AD, i.e., not accompanied by bronchial asthma. The objectives of our study were :I) To examine the growth pattern of children suffering from â€˜pureâ€ AD and ii) to ascertain the relationship, if any, of selected disease parameters with growth attainments of children. A total of 108 children (63 males and 45 females), aged 1-5+ years with â€˜pureâ€ AD were aross-sectionally examined for selected anthropometric parameters including height, weight, mid- upper arm circumference and biceps and triceps skin fold thickness. Fifty eight (54%) subjects weighed below the 10th centile and 23 (28%) were below the 10th centile for height of the NCHS standards. Boys showed relatively worse growth performance than girls from 1-4 years of age. There was no significant correlation between disease severity of extent and growth attainments. Our findings point to an impaired somatic growth in pre-school children with AD, boys faring worse than the girls, and to no association of growth performance with severity or extent of the disease